Port Alliances Concept: A Way Forward - Shahrin Nasir; Mohd Faiz Hakim (International Journal of Supply Chain Management, 2017)
This paper is focusing on the way forward for world port alliances. Many ports operators such as HPH, APMT and ODW own a few ports in the world. By looking at that development, small and medium port operators left alone in competing the in the competitive market. By comprehending the concept of alliances which is strongly used in many transport operators such as airline industry, it would rebrand the ports operators worldwide. The discussion on how the alliances should be materialised and the benefits of having these alliances are well structured in the paper. With the input form a port operator, it has identified the key areas alliances can capitalise and it would enhance the productivity and efficiency of the ports operations. With the global business expanding, world port alliances would be able to change and spur further development in the fast moving maritime business.